FAKTOR YANG MEMENGARUHI KEJADIAN EPILEPSI PASCASTROKE DI RSUP DR HASAN SADIKIN - Indrs Gunawan Affandi; Suryani Gunadharma; Anam Ong (PERDOSNI, 2020)
FACTORS THAT INFLUENCE POSTSTROKE EPILEPSY IN DR HASAN SADIKIN HOSPITALABSTRACTIntroduction:Stroke is the most commonly identified cause of epilepsy in adult. Stroke patients with cortical involvement, hemorrhagic stroke, severe neurological deficits, and old age are factors which influence the incidence of poststroke epilepsy.Aim: This research was to analyse factors which influence the incidence of poststroke epilepsy in Dr. Hasan Sadikin Hospital, Bandung.Method:The case-control study was performed retrospectively from 1725 stroke patients in dr. Hasan Sadikin Hospital Bandung during the period of January 2014-December 2016. Mann-Whitney statistical analysis, Spearman rank and logistic regression were performed to see the relationship between neurological deficits during onset of stroke, patient age, location of lesions and stroke type on poststroke epilepsy. Neurologic deficits were assessed by National Institutes of Health Stroke Scale (NIHSS), location of lesions and stroke types assessed by Brain CT Scan or MRI, old age was >60 years.Results: Poststroke epilepsy occurred in 53 patients, but only 47 patients met the case group criteria and 94 control group patients totaling 141 subjects. More than half (52.6%) of cortical lesions had poststroke epilepsy. Severe neurologic deficits developed into poststroke epilepsies in 45.8%. Stroke type and age did not influence the incidence of poststroke epilepsy (p=0,843, OR=0,93).Discussion:Cortical lesions cause three-fold poststroke epilepsy and severe neurological deficits cause twice as many poststroke epilepsy events.Keyword: Cortical lesion, poststroke epilepsy, severe neurological deficitsPendahuluan: Stroke merupakan penyakit yang sering mengakibatkan epilepsi pada orang dewasa. Lokasi di kortikal, jenis stroke perdarahan, defisit neurologis yang berat serta usia tua merupakan faktor-faktor yang memengaruhi terjadinya epilepsi pascastroke.Tujuan: Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi kejadian epilepsi pascastroke di RSUP Dr. Hasan Sadikin, Bandung.Metode: Penelitian kasus kontrol dilakukan secara retrospektif pada 1725 pasien stroke di RSUP dr. Hasan Sadikin Bandung selama periode Januari 2014–Desember 2016. Analisis statistik Mann-Whitney, rank Spearman dan regresi logistik dilakukan untuk melihat hubungan antara defisit neurologis saat awitan stroke, usia pasien, lokasi lesi dan jenis stroke terhadap kejadian epilepsi pascastroke. Defisit neurologis dinilai dengan skor National Institute of Health Stroke Scale (NIHSS), lokasi lesi dan jenis stroke dinilai dengan CT scan otak atau MRI, usia tua adalah >60 tahun.Hasil: Epilepsi pascastroke terjadi pada 53 pasien, tetapi hanya 47 pasien yang memenuhi kriteria kelompok kasus dan 94 pasien kelompok kontrol sehingga total 141 subjek penelitian. Sebanyak 52,6% lesi stroke di kortikal menjadi epilepsi pascastroke. Defisit neurologis berat berkembang menjadi epilepsi pascastroke sebanyak 45,8%. Jenis stroke dan usia tidak memengaruhi kejadian epilepsi pascastroke.Diskusi: Lesi kortikal menghasilkan kejadian epilepsi pascastroke sebanyak tiga kali lipat dan defisit neurologis berat menghasilkan kejadian epilepsi pascastroke sebanyak dua kali lipat.Kata kunci: Defisit neurologis berat, epilepsi pascastroke, lesi kortikal